PEMANFAATAN PELAYANAN PEMERIKSAAN KEHAMILAN DI WILAYAH KERJA PUSKESMAS LANGKIMAT KABUPATEN PADANG LAWAS UTARA TAHUN 2013 - SARIANI .; SARMA N; IMAM MUHAMMAD (JURNAL ILMIAH MAKSITEK, 2020)
High maternal mortality in Indonesia is realited to many factor, including the quality of the behavior of Pregnancy women thatmany still do not avail of pregnancy examination at the ministry of health, so that high-risk pregnancy and thisis theproblemin the field of the health. Based on reports from clinics that target Langkimat of pregnancy women recorded in 2012who checked her pregnancy to a health care facility that is as many as 377 K1 (48.8) and K4 as much as 374 people(48.4).The purpose of this research is to analyze the relationshing of factors predisposing, factors supporting and driving factor. Theresearch tyfe is explanatory research. The population in this research are all the pregnancy women in the region in 2012Langkimat health centers North Padang Lawas regency totaled 323 people who recorded from January to December 2012.While the example as many as 95 people. Method of data collection using test validity and reliability tests are obtainedthrough the research data using univariate, bivariat.). The results showed that there is no relationship of factors predisposinglike age (p 0.573) and number of children (p 0.689) towards avail of pregnancy examination services.Predisposing factorsuch as education (p 0.000), knowledge (p 0.002) and attitude (p 0.000) prenancy examination against relationships. Thereis a relationship of factor endowments such as income (p.0.000), exposure media (p 0.001) against the gestational avail.There is a relationship of the driving factor as support the husband (p 0.017), support of the health care personnel (p 0.000)against pregnancy checkup. It is recommended to pregnancy women in order to make a visit to the site of the ministry ofheath aswell as consultation to midwivesabaut the pregnancy examination sa as to enhance the knowledge of pregnancywomen throung the question and answer. Expected related to local governments in ordre to participate actively in theprogramme of the visit of inspection visits with each pregnancy clinics and heath in order to improve pasyandu pregnantwomen and children.